First-Century Christians in Twenty-First Century Africa : Between Law and Grace in Gabon and Madagascar - Devir, Nathan P., (Studies of Religion in Africa ;, 2022)
Millions of African Christians who consider themselves genealogical descendants of one of the Ten Lost Tribes of Israel-in other words, Jewish by ethnicity, but Christian in terms of faith-are increasingly choosing a religious affiliation that honors both of these identities. Their choice: Messianic Judaism. Messianic adherents emulate the Christians of the first century, observing the Jewish commandments while also affirming the salvational grace of Yeshua (Jesus). As the first comparative ethnography of such "fulfilled Jews" on the African continent, this book presents case studies that will enrich our understanding of one of global Christianity's most overlooked iterations.